Advantage of Recording Single-Unit Muscle Sympathetic Nerve Activity in Heart Failure - MURAI, HISAYOSHI; Takamura, Masayuki; Kaneko, Shuichi (Frontiers in Physiology, 2012)
Elevated sympathetic activation is a characteristic feature of heart failure (HF). Excessive sympathetic activation under resting conditions has been shown to increase from the early stages of the disease, and is related to prognosis. Direct recording of multiunit efferent muscle sympathetic nerve activity (MSNA) by microneurography is the best method for quantifying sympathetic nerve activity in humans. To date, this technique has been used to evaluate the actual central sympathetic outflow to the periphery in HF patients at rest and during exercise; however, because the firing occurrence of sympathetic activation is mainly synchronized by pulse pressure, multiunit MSNA, expressed as burst frequency (bursts/min) and burst incidence (bursts/100heartbeats), may have limitations for the quantification of sympathetic nerve activity. In HF, multiunit MSNA is near the maximum level, and cannot increase further than the heartbeat. Single-unit MSNA analysis in humans is technically demanding, but provides more detailed information regarding central sympathetic firing. Although a great deal is known about the response of multiunit MSNA to stress, little information is available regarding the responses of single-unit MSNA to physiological stress and disease. The purposes of this review are to describe the differences between multiunit and single-unit MSNA during stress and to discuss the advantages of single-unit MSNA recording in improving our understanding the pathology of increased sympathetic activity in HF.